Accurate fault location of complex distribution network with distributed generators. Issue 13 (12th December 2017) - Li, Weijian; Guo, Chuangxin; Jin, Yu; Gong, Xiao
Abstract : For the complex distribution network with lots of branches and distributed power supply, a fault location method based on voltage sag information is proposed. First, the equivalent model is established for the distributed power source. Then the fault current vector is obtained by using the node impedance matrix and the voltage vector recorded by the distributed power supply access point before and during the fault. Finally, the faulted node is determined by comparing fault current deviation values. Through the simulation analysis of an actual complex distribution network, the validity and efficiency of the proposed method is verified, and the influence of load fluctuation and transition resistance is small.